Peran Guru PAI dalam Pembentukan Karakter Religius untuk Mengatasi Dampak Media Digital pada Siswa di SD Negeri 1 Karanggude - Muhammad Sulthan Zukhruf; Nurkholis Nurkholis (An-Nahdloh: Journal of Education and Islamic Studies, 2026)
This study aims to analyze the role of Islamic Religious Education (PAI) teachers in shaping students’ religious character as an effort to overcome the negative impacts of digital media on elementary school students. The rapid development of digital technology has influenced students’ behavior, learning motivation, communication patterns, and spiritual attitudes, especially at the elementary level, where children are more vulnerable to uncontrolled digital exposure. This study used a descriptive qualitative method conducted at SD Negeri 1 Karanggude. The findings show that the PAI teacher carries out three essential roles as a muallim, murabbi, and muaddib through knowledge transfer, habituation of religious practices, and character cultivation based on Islamic values. Various strategies are employed, including integrating religious values into learning, strengthening daily routines such as prayer and recitation, providing exemplary behavior, and developing emotional closeness with students. These efforts effectively foster students’ religious character and reduce negative digital influences such as reduced discipline, weakened worship habits, and inappropriate communication patterns. The study concludes that the role of the PAI teacher is crucial in guiding students amidst the challenges of the digital era through holistic and value-based character education.   Keywords: Digital media, Islamic religious education teacher, religious character, elementary school, character formation.